Plagiarism in academic writing: the case of EFL students in higher education - Fernández López, Sofía (2017)
Nowadays, undergraduates have access to information faster and easier because of the Internet. This phenomenon has facilitated dishonesty practices among students, to mention one: Academic plagiarism. This concept is derived from a lack of Academic Integrity. Academic Integrity and Plagiarism vary from different cultures. In fact, according to McDonnell (2004), undergraduates might plagiarize because of different factors, to mention one: lack of academic writing skills (especially non-English native speakers). This action research project took place at Universidad Autónoma de Nuevo León (UANL) in San Nicolás de Los Garza, Nuevo León. The participants are 38 English as Foreign Language (EFL) undergraduates of 10th semester from the major of Sciences of language. This didactic proposal aims at finding out if there is any relationship between the students’ level of plagiarism, lack of academic writing skills, and plagiarism awareness. The participants answered a validated Likert-scale survey to discover how much they know about plagiarism, and then they were asked to write an essay as part of their academic program to verify their actual level of plagiarism and academic writing skills. The data gathered were analyzed through an SPSS program to get the correlation between the variables (lack of academic writing and plagiarism). The results demonstrated that students are aware of plagiarism. Even though, SPSS showed that the lack of academic writing skills is one of the factors that lead undergraduates to do plagiarism. Therefore, this proposal will benefit undergraduates to be aware of their level of plagiarism by educating professors about the importance of academic integrity and providing them with tools that might help detect academic dishonesty practices.